Lepidopteran fauna of the city of Karaganda - Abukenova, V.S.; Kaptyonkina, A.G. (KSU Publ., 2020)
In the article the results of investigation of the species composition of Lepidoptera in city of Karaganda are presented. Studies were conducted in urban parks, squares, courtyards and areas around Karaganda city. Representatives of 11 families, 35 species were identified. The bio indication value of Lepidoptera in monitoring researches is due to their significant role and large biomass in the natural communities, rapid change of the generation, high fecundity and sensitivity to a big number of anthropogenic impact. According to preliminary data, the butterflies of the families Nimphalidae, Satyridae were the most numerous. Background species are Nymphalis urtical L., Melitaea didyma, Hyponephele lycaon Rott. Small and decorating nature species have been identified. In result was made the booklets, which called «Rare and endangered butterflies of the Central Kazakhstan» for the Museum of Nature of E.A. Buketov Karagandа State University. These species must be monitored in the Karaganda city. Refined data on species are pests. Some species are recommended for collecting and training in summer subject schools or at Universities in entomology classes. Further, it is planned to study the distribution of Lepidoptera in the city.
Қарағанды қаласының лепидоптер фаунасы
Фауна чешуекрылых города Караганды
Keywords: fauna of the city; Nymphalidae; Satyridae; urban ecosystem; species adorning nature; insects; Lepidoptera; butterflies